2011
DOI: 10.3892/or.2010.1106
|View full text |Cite
|
Sign up to set email alerts
|

Categorical meta-analysis of Osteopontin as a clinical cancer marker

Abstract: Abstract. Although extensive literature exists on cancer biomarkers few have found entry into clinical use. In particular, the cancer metastasis gene Osteopontin has been investigated extensively but it has not yet been applied to routine diagnostics. Here, we conduct a meta-analysis of data from the published literature and from RNA microarrays deposited in Oncomine. Osteopontin has been associated with 34 cancers. It is a marker for breast, cervical, colorectal, head and neck, liver, lung, ovarian and prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 26 publications
(40 reference statements)
4
49
0
2
Order By: Relevance
“…Notably, although the link between overexpression of osteopontin and worse outcome is clear, meta-analysis of osteopontin in breast cancer concluded that osteopontin expression is independent of breast cancer subtypes (42). However, the role of tumor-derived osteopontin in modulating the tumor microenvironment is largely unresolved.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, although the link between overexpression of osteopontin and worse outcome is clear, meta-analysis of osteopontin in breast cancer concluded that osteopontin expression is independent of breast cancer subtypes (42). However, the role of tumor-derived osteopontin in modulating the tumor microenvironment is largely unresolved.…”
Section: Discussionmentioning
confidence: 99%
“…Osteopontin expression has been associated with breast cancer progression, regardless of the histologic subtype of the cancer (4,6). Importantly, the polymorphic site at -443, but not -1748 or -1776, showed differences between ER-positive and ER-negative breast cancers and between PR-positive and PR-negative breast cancers, but there was no association with HER2 status.…”
Section: Resultsmentioning
confidence: 91%
“…Osteopontin is a metastasis-related gene that contributes to the progression of over 30 forms of cancer (3)(4)(5). Aberrant splicing of osteopontin in cancers has been accounted for by our identification of the variant form osteopontin-c, which is selectively expressed in cancer cells but is absent from non-transformed cells (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…As a multi-functional cytokine, OPN is involved in cell survival, migration and adhesion which is associated with tumorigenesis, progression and metastasis. OPN is also implicated in tumorgenesis and has been proposed as a cancer marker including nasopharyngeal carcinoma, lung cancer, colon cancer and prostate cancer [10,11]. …”
Section: Introductionmentioning
confidence: 99%